2018
DOI: 10.1111/bcp.13598
|View full text |Cite
|
Sign up to set email alerts
|

Reducing potentially inappropriate drug prescribing in nursing home residents: effectiveness of a geriatric intervention

Abstract: This intervention based on a global geriatric education resulted in a significant reduction of PIDP at patient level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 55 publications
0
19
1
Order By: Relevance
“…Five trials performed in European Union (EU) countries NHs were published after these SRs and are summarized in Table 1 [11,[17][18][19][20]. These were all multicenter studies-three were cluster-randomized controlled trials-and involved multidisciplinary interventions mainly consisting of education of HCPs and MR. None involved a CDSS component.…”
Section: Interventions To Optimize Prescribing For the Whole Medicatimentioning
confidence: 99%
“…Five trials performed in European Union (EU) countries NHs were published after these SRs and are summarized in Table 1 [11,[17][18][19][20]. These were all multicenter studies-three were cluster-randomized controlled trials-and involved multidisciplinary interventions mainly consisting of education of HCPs and MR. None involved a CDSS component.…”
Section: Interventions To Optimize Prescribing For the Whole Medicatimentioning
confidence: 99%
“…study and our analysis: in our investigation, the most frequently prescribed PIMs within the classe of benzodiazepines and antipsychotics were lorazepam (at a daily dose of 2 mg or more) and olanzapine (at a daily dose of 10 mg or more), respectively, as opposed to bromazepam and risperidone in the Cool et al. study 31 . This is remarkable because the German PRISCUS list considers risperidone as a drug with an overall favorable benefit‐to‐risk profile in elderly patients and as a suitable alternative to first‐generation antipsychotics and olanzapine (>10 mg/d) 15 …”
Section: Discussionmentioning
confidence: 58%
“…As information on MRPs in gerontopsychiatric inpatients is scarce, we compared our results with the data published by Cool and colleagues who investigated the frequency of potentially inappropriate drug prescribing in French nursing home residents 31 . Of note, the MRP definition used in our study included the definition of potentially inappropriate drug prescribing used in the Cool et al.…”
Section: Discussionmentioning
confidence: 97%
“…Numerous studies have also shown the effect of targeted interventions comprising different health care professionals and methods of reducing the overall consumption of medications in nursing homes. In particular, interprofessional (nurse, pharmacist, general practitioner) interventions that involve medication review with a pharmacist [ 13 , 23 ]; specialised geriatric education for nursing home staff [ 24 ], auditing prescriptions based on geriatric risk assessment [ 25 ]; or retrospective drug utilization review activities have all been effective in improving the quality of prescriptions [ 26 ].…”
Section: Discussionmentioning
confidence: 99%